The Effect of Teacher Working Groups (Kelompok Kerja Guru/KKG) on the Pedagogical Competence and Performance of Elementary School Teachers in South Touluaan District, Southeast Minahasa Regency - Gloria Ritsita Lengkong; Richard D.H. Pangkey; Aldjon N. Dapa (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to examine the influence of the Teacher Working Group (Kelompok Kerja Guru/KKG) on the pedagogical competence and performance of elementary school teachers in South Touluaan District, Southeast Minahasa Regency. Teacher competence, especially pedagogical competence, plays an important role in improving the quality of learning and student outcomes. The KKG serves as a professional forum for teachers to collaborate, share experiences, and improve their teaching skills. However, its implementation is not yet fully optimal. Therefore, this study investigates the extent to which participation in KKG contributes to improving teachers’ pedagogical competence and performance in the classroom. The results of this study are expected to provide input for improving teacher professional development programs. Keywords: Teacher Working Group (KKG), pedagogical competence, teacher performance, elementary school teachers, professional development